Associations between the misinformation effect, trauma exposure and symptoms of posttraumatic stress disorder and depression. Issue 2 (7th February 2023) - Jobson, Laura; Wade, Kimberley A.; Rasor, Samantha; Spearing, Emily; McEwen, Cassandra; Fahmi, Danielle
ABSTRACT: This research aimed to conduct an initial investigation into the relationships between the "misinformation effect" and trauma exposure, posttraumatic stress disorder (PTSD) and depression. Study 1 was a pilot study developing an online misinformation paradigm that could assess the influence of emotion and arousal on memory distortions. Participants ( n  = 162, Mage  = 39.90; SD  = 10.90) were recruited through TurkPrime. In Study 2 community members ( n  = 116, Mage  = 28.96; SD  = 10.33) completed this misinformation paradigm and measures of trauma exposure, PTSD, and depression. Study 1 found memory for central details was better for high-arousal than low-arousal and neutral-arousal images. Peripheral memory appeared worse for negative and neutral images than positive images. Study 2 found that, when controlling for age and gender, PTSD symptoms significantly predicted proportion of correct responses on control items. However, there was no evidence to indicate that trauma exposure, PTSD symptoms nor depression symptoms, were associated with proportion of correct responses on misled items. Valence and arousal did not influence these associations. These findings have important implications in clinical and legal contexts where individuals with a history of trauma, or who are experiencing symptoms of PTSD or depression, are often required to recall emotionally-laden events. There is a surprising dearth of research into the misinformation effect in clinical populations and further research is required.